REVITALISASI PIC STUNTING DI 10 DESA LOKUS STUNTING TAHUN 2023 SEBAGAI UPAYA PERCEPATAN PENURUNAN STUNTING KABUPATEN PAMEKASAN - Nugrahani, Cantika Iva; Noviandry R, Hilmah; Christiana, Elisa; Setya Ferdina, Cucun; Sari, Agoesta Pralita; Amin, Edy Suryadi; Rahman, Taufiqur; Iszakiyah, Nur; Rahmawati, Sylvina; Rochmah, Ibtisam Nailatur (Jurnal Abdimas Bina Bangsa, 2025)
The “zero Hunger” target of the Sustainability Development Goals (SDGs) is to eliminate all forms of malnutrition by 2030 and reduce the prevalence of stunting in children by 50% (United Nations, 2015). In 2022, the Pamekasan Health Office succeeded reducing the incidence of stunting in a significant time, namely from 38.6% in 2021 to 8.1% in 2022 (SSGI, 2022). The next urgency is to maintain this positive achievement and ensure that there are no more additional cases of stunting, by looking at the results of the evaluation of the implementation of the strategy, namely optimizing the active role of the community to support stunting prevention actions (LKJIP Health Office, 2021). Thus, one of the programs was created, namely the Revitalization Of PIC Stunting in 10 stunting village locations in Pamekasan Regency 2023. The purpose of this activity is to improve the knowledge and skills of PIC Stunting in efforts to prevent and manage reporting of stunting cases. This activity was attended by 23 participants consisting of 17 PIC Stunting, 4 people from the Pamekasan Health Office, and 2 people from DP3AP2KB. The core activity was in presentation of material from analytical speakers in the form of problems, strategies to accelerate stunting reduction, socialization of the SOBAT GESIT application, discussion, and closed with the provision a module " Langkah Mewujudkan Generasi Emas Bebas Stunting". This PIC Stunting Revitalization Program produced outputs in the form of a joint commitment in efforts to accelerate stunting reduction in Pamekasan Regency.